Centre for Transport Research University of Zilina - Fabian, Peter (Communications - Scientific letters of the University of Zilina, 2003)
CETRA – Institute of Transport at the University of Žilina has been selected for support by the European Commission within the “Support for Research Infrastructures in the New Associated States” project within the EU 5th Framework Programme. The support is oriented and used towards organisation of international conferences, workshops, participation in the international conferences and workshops, publication of research results and longterm working stages of scientific staff at CETRA.